Modelling the Spread of Foot and Mouth Disease in Different Livestock Settings in Italy to Assess the Cost Effectiveness of Potential Control Strategies - Michele Pesciaroli; Alessandro Bellato; Alessandra Scaburri; Annalisa Santi; Alessandro Mannelli; Silvia Bellini (Animals)
Foot and Mouth disease (FMD) transmission is strongly related to the distribution and density of FMD-susceptible animals. In this study, we applied a model to simulate the spread of FMD in three Italian regions with different livestock demographics (densely, medium, and sparsely populated) in order to assess the cost effectiveness of the disease control options within the framework of the Italian contingency plan. The results of the simulations showed that stamping-out was sufficient to control the outbreak in the sparsely and medium populated areas whereas, in densely populated areas, only vaccinations could effectively control an outbreak. We also estimated the economic resources needed for the adoption of different control strategies, considering livestock indemnity, cleaning, disinfection and disposal, surveillance, vaccination and personnel costs. The results obtained showed that indemnity due to culling had the highest impact on the costs in all scenarios and vaccination resulted in the most cost-effective option to apply in densely populated livestock areas. The results of this study can be a useful aid to Competent Authorities in the preparation of contingency plans against FMD.